2020
DOI: 10.1111/cxo.12947
|View full text |Cite
|
Sign up to set email alerts
|

Optical changes and visual performance with orthokeratology

Abstract: Orthokeratology has undergone drastic changes since first described in the early 1960s. The original orthokeratology procedure involved a series of lenses to flatten the central cornea and was plagued by variable results. The introduction of highly oxygen‐permeable lens materials that can be worn overnight, corneal topography, and reverse‐geometry lens designs revolutionised this procedure. Modern overnight orthokeratology causes rapid, reliable, and reversible reductions in refractive error. With modern desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 110 publications
(212 reference statements)
1
43
0
Order By: Relevance
“…Chen et al [61] described a statistically significant rise in spherical aberrations (0.05 ± 0.6 to 0.19 ± 0.13 µm) and coma aberrations (0.12 ± 0.19 to 0.36 ± 0.23 µm). Other authors found similar results and conclusions [49,[66][67][68][69]. Some authors related this increase in aberrations with the decrease in the corneal thickness [70] with contact lens use of approximately 20 µm [61], although Guo et al [71] did not consider these significant changes after seven years of follow-up, coinciding with other studies that did not find changes in the endothelial cell density [72,73].…”
Section: Orthokeratologymentioning
confidence: 59%
See 1 more Smart Citation
“…Chen et al [61] described a statistically significant rise in spherical aberrations (0.05 ± 0.6 to 0.19 ± 0.13 µm) and coma aberrations (0.12 ± 0.19 to 0.36 ± 0.23 µm). Other authors found similar results and conclusions [49,[66][67][68][69]. Some authors related this increase in aberrations with the decrease in the corneal thickness [70] with contact lens use of approximately 20 µm [61], although Guo et al [71] did not consider these significant changes after seven years of follow-up, coinciding with other studies that did not find changes in the endothelial cell density [72,73].…”
Section: Orthokeratologymentioning
confidence: 59%
“…This also provides freedom for participation in sports activities. A new study [49] reviewed different works on the effects of OK, reporting a better quality of life and satisfaction with vision by patients who completed a visual scale. Findings have shown orthokeratology to be effective in slowing axial elongation.…”
Section: Overnight Orthokeratology Efficacymentioning
confidence: 99%
“…Following overnight reshaping of the anterior corneal surface from a prolate to an oblate shape, the eye exhibits a significant decrease in spherical refractive error and an increase in corneal and total ocular higher order aberrations (HOA's). 2 The most notable changes in the HOA profile are a positive shift in primary spherical aberration 3 and variations in horizontal and vertical coma related to treatment zone centration, 4 which result in an increase in higher order root mean square error values (HO RMS) that typically stabilises after one to four weeks of lens wear. 5 Since HOA's cannot be corrected with a conventional sphero-cylindrical refraction they may potentially influence eye growth through a vision-dependent mechanism by altering retinal image quality, or providing a directional cue through variations in optical vergence across the pupil.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact optical mechanism underlying the myopia control effect of orthokeratology remains unclear. Following overnight reshaping of the anterior corneal surface from a prolate to an oblate shape, the eye exhibits a significant decrease in spherical refractive error and an increase in corneal and total ocular higher order aberrations (HOA’s) 2 . The most notable changes in the HOA profile are a positive shift in primary spherical aberration 3 and variations in horizontal and vertical coma related to treatment zone centration, 4 which result in an increase in higher order root mean square error values (HO RMS) that typically stabilises after one to four weeks of lens wear 5 .…”
Section: Introductionmentioning
confidence: 99%
“…While it is now well accepted that overnight orthokeratology treatment significantly slows myopia progression in children, the underlying optical mechanism remains unclear. Nti and Berntsen review the optics of modern overnight reverse geometry orthokeratology lens designs including their effects on accommodation, peripheral refraction and on axis higher order aberrations. Lau et al also report on the change in the higher order aberration profile by modifying the Jessen factor in paediatric orthokeratology for myopia control.…”
mentioning
confidence: 99%